Episode-based payment variation for urological cancer surgery - Ellimoottil, Chad (Urology, 2017)
OBJECTIVE: To investigate payment variation for three common urological cancer surgeries and evaluate the potential for applying bundled payment programs to these procedures. METHODS: Using 2008–2011 Surveillance, Epidemiology, and End Results-Medicare linked data, we identified all beneficiaries aged greater than 65 years who underwent cystectomy, prostatectomy, or nephrectomy for cancer. Total episode payments were determined by aggregating hospital, professional, and post-acute care claims from the index surgical hospitalization through 90 days post-discharge. Total episode payments were then compared to examine hospital level-variation within each procedure type and the specific payment components (i.e. index hospitalization, professional, readmission, and post-acute care) driving spending variation. RESULTS: Ninety-day episodes of care were identified for 1,849 cystectomies, 8,770 prostatectomies, and 4,304 nephrectomies. We observed wide variation in mean episode payments for all three conditions (cystectomy mean $35,102: range $24,112 to $57,238, prostatectomy mean $10,803: range $8,816 to $17,877, nephrectomy mean $17,475: range $11,681 to $26,711). Majority of payment variation was attributable to index hospitalization and post-acute care for cystectomy and nephrectomy and professional payments for prostatectomy. The most expensive hospitals by procedure each demonstrated a unique opportunity for spending reduction due to individual differences in component payment patterns between hospitals. CONCLUSION: Ninety-day episode payments for urological cancer surgery vary widely across hospitals in the United States. The key drivers of this payment variation differ for individual procedures and hospitals. Accordingly, hospitals will need individualized data and clinical re-design strategies to succeed with implementation of episode-based payment models for urological cancer care.